Pengembangan Lembar Kerja Peserta Didik Berbasis Higher Order Thinking Skills pada Pembelajaran Tematik Muatan IPA Kelas V Tema 3 Subtema 1 - Khafiza, Asha Quranul; Kresnadi, Hery; Suparjan, Suparjan; Halidjah, Siti; Pranata, Rio (AS-SABIQUN, 2023)
The product of student worksheets (LKPD) based on Higher Order Thinking Skills (HOTS) for thematic learning of science content on the human and animal digestive systems is the aim of this research. In addition, it also aims to find out whether or not elementary schools can implement student worksheet products (LKPD) based on higher order thinking skills (HOTS) for thematic learning of science class V theme 3 sub-theme 1. By adopting the ADDIE design development model, research and development (RnD) was used as the research method. The analysis, design, development, implementation, and evaluation stages are the HOTS-based LKPD development process. The results of the validation of the four validators and student response trials became a source of research data. Validator validation questionnaires and student response questionnaires during product trials became the method of collecting data for this study. To find out the validity of the product, validation questionnaires were distributed to class teachers, linguists, design experts, and material experts. Limited trials and wide trials are two phases of trials. The material aspect of LKPD feasibility validation produces an average score of 4.2 with very valid criteria. The feasibility of the language aspect gets an average score of 4.8 with very valid criteria, and the feasibility of the design aspect gets an average score of 3.9 with a valid category. The test results obtained an average score of fifth grade students' limited trials was 4.6 and the average value of fifth grade students' wide trials was 4.5. So that it can be stated that the HOTS-based LKPD can and is fully feasible for use in learning.